1998
DOI: 10.2190/7vrq-ebw0-vrw7-d0u9
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the Stress of Immigration among New Immigrants to Israel from Commonwealth of Independent States (CIS) Who Were Exposed to Chernobyl: The Effect of Age

Abstract: This study examined the differential effect of age on coping and psychological measures among immigrants from Commonwealth of Independent States (CIS) to Israel. Some of these immigrants originated in the Republics adjacent to the Chernobyl Power Plant, site of the 1986 accident. The sample consisted of 708 immigrants who were interviewed between the years 1993-1995 with an average age of 47.5 (sd 11.8). This sample was reinterviewed approximately a year and three months later (n = 520). The sample included tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…One study concerned a selected group of immigrants who came from the Chernobyl area. The authors reported that the improvement in depressive symptoms over time (15 months) was slower among the elderly than among the non-elderly (Cwikel and Rozovski, 1998). Contrary to this, the results of the other study did not indicate age-related differences in psychological distress (Ritsner and Ponizovsky, 1998).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…One study concerned a selected group of immigrants who came from the Chernobyl area. The authors reported that the improvement in depressive symptoms over time (15 months) was slower among the elderly than among the non-elderly (Cwikel and Rozovski, 1998). Contrary to this, the results of the other study did not indicate age-related differences in psychological distress (Ritsner and Ponizovsky, 1998).…”
Section: Discussionmentioning
confidence: 69%
“…Other studies carried out among Russian immigrants to Israel (Cwikel and Rozovski, 1998;Ritsner and Ponizovsky, 1998) addressed the assessment of symptoms of distress, but not rates of clinical disorders, and did not control for time passed since immigration. Results were con¯icting.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, PTSD symptom severity in former prisoners of war in WWII and the Korean War was negatively associated with their age at capture (Dikel, Engdahl, & Eberly, 2005). In contrast, older immigrants exposed to either the Oklahoma City bombing or the Chernobyl power plant accident (Trautman et al, 2002; Cwikel & Rozovski, 1998, respectively) were at greater risk of PTSD than were younger immigrants. Greater immigration‐related stress among older immigrants was hypothesized to be one of the factors associated with their increased vulnerability to PTSD (Cwikel & Rozovski, 1998).…”
mentioning
confidence: 96%
“…In this review, there were 24 category A studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], 10 category B studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and only 1 category C study [ 48 ]. The list of included studies is given in Supplementary Material 2 .…”
Section: Resultsmentioning
confidence: 99%